Aberrant Whole-Brain Functional Connectivity and Intelligence Structure in Children with Primary Nocturnal Enuresis - Yu, Bing; Sun, Hongbin; Ma, Hongwei; Peng, Miao; Kong, Fanxing; Meng, Fanxing; Liu, Na; Guo, Qiyong (PloS one, 2013)
To assess the potential relationship between intelligence structure abnormalities and whole-brain functional connectivity in children with primary nocturnal enuresis (PNE) with resting-state functional magnetic resonance imaging (fMRI) to provide insights into the association between these two seemingly unrelated conditions. Intelligence testing and fMRI data were obtained from 133 right-handed children, including 67 PNE children (M/F, 39:28; age, 10.5 ± 1.2 y) and 66 age-matched healthy controls (M/F, 37:29; age, 10.1 ± 1.1 y). All intelligence tests were performed using the China-Wechsler Intelligence Scale for Children (C-WISC). Each subject's full intelligence quotient (FIQ), verbal IQ (VIQ), performance IQ (PIQ), and memory/caution (M/C) factor was measured and recorded. Resting state fMRI scans were performed on a 3.0-T MR scanner and post-processed using REST software. Comparisons of z-score correlation coefficients between distinct cerebral regions were used to identify altered functional connectivity in PNE children. The PNE group had normal FIQ, VIQ, and PIQ values, indicating no significant variation from the control group. However, the M/C factor was significantly lower in the PNE group. Compared to the control group, PNE children exhibited overall lower levels of functional connectivity that were most apparent in the cerebello-thalamo-frontal pathway. The M/C factor significantly correlated with z-scores representing connectivity between Cerebellum_Crus1_L and Frontal_Mid_R. PNE children exhibit intelligence structure imbalance and attention deficits. Our findings suggest that cerebello-thalamo-frontal circuit abnormalities are likely to be involved in the onset and progression of attention impairment in PNE children.